Measuring executive function skills in young children in Kenya. Issue 4 (19th May 2019) - Willoughby, Michael T.; Piper, Benjamin; Kwayumba, Dunston; McCune, Megan
ABSTRACT: Interest in measuring executive function skills in young children in low- and middle-income country contexts has been stymied by the lack of assessments that are both easy to deploy and scalable. This study reports on an initial effort to develop a tablet-based battery of executive function tasks, which were designed and extensively studied in the United States, for use in Kenya. Participants were 193 children, aged 3–6 years old, who attended early childhood development and education centers. The rates of individual task completion were high (65–100%), and 85% of children completed three or more tasks. Assessors indicated that 90% of all task administrations were of acceptable quality. An executive function composite score was approximately normally distributed, despite higher-than-expected floor and ceiling effects on inhibitory control tasks. Children's simple reaction time ( β  = –0.20, p  = .004), attention-related behaviors during testing ( β  = 0.24, p  = .0005), and age ( β  = –0.24, p  = .0009) were all uniquely related to performance on the executive function composite. Results are discussed as they inform efforts to develop valid and reliable measures of executive function skills among young children in developing country contexts.